2023
DOI: 10.1021/acs.accounts.2c00851
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Tools for Lipid Cell Biology

Abstract: Conspectus Lipids are key components of all organisms. We are well educated in their use as fuel and their essential role to form membranes. We also know much about their biosynthesis and metabolism. We are also aware that most lipids have signaling character meaning that a change in their concentration or location constitutes a signal that helps a living cell to respond to changes in the environment or to fulfill its specific function ranging from secretion to cell division. What is much less understood is ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…13,14 Trifunctional lipids add three functional groups to the endogenous lipid structure: (1) a terminal alkyne, for click chemistry with affinity tags or fluorophores, (2) a diazirine for photocrosslinking with interacting proteins, and (3) a photocage to prevent premature metabolism and signaling. 13,14 Here, we investigated the metabolism and subcellular localization of both probes and showed that while the two sphingoid bases result in nearly identical pools of metabolites, the two lipids have subtle differences in their subcellular dynamics. Finally, we performed LC-MS/MS-based identification of probeinteracting proteins and described a network of lipidinteracting proteins with both distinct and overlapping interactions for each lipid base.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Trifunctional lipids add three functional groups to the endogenous lipid structure: (1) a terminal alkyne, for click chemistry with affinity tags or fluorophores, (2) a diazirine for photocrosslinking with interacting proteins, and (3) a photocage to prevent premature metabolism and signaling. 13,14 Here, we investigated the metabolism and subcellular localization of both probes and showed that while the two sphingoid bases result in nearly identical pools of metabolites, the two lipids have subtle differences in their subcellular dynamics. Finally, we performed LC-MS/MS-based identification of probeinteracting proteins and described a network of lipidinteracting proteins with both distinct and overlapping interactions for each lipid base.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To begin to unravel the cell biological differences between Spa and Sph, we synthesized trifunctional sphinganine to compare to the previously described trifunctional sphingosine . Trifunctional lipids are designed to overcome several challenges in interrogating lipid biology: their fast metabolism, their weak and transient (but functionally important) interactions with proteins, and the difficulty in tagging them without disturbing the cellular location. , Trifunctional lipids add three functional groups to the endogenous lipid structure: (1) a terminal alkyne, for click chemistry with affinity tags or fluorophores, (2) a diazirine for photo-crosslinking with interacting proteins, and (3) a photocage to prevent premature metabolism and signaling. , Here, we investigated the metabolism and subcellular localization of both probes and showed that while the two sphingoid bases result in nearly identical pools of metabolites, the two lipids have subtle differences in their subcellular dynamics. Finally, we performed LC-MS/MS-based identification of probe-interacting proteins and described a network of lipid-interacting proteins with both distinct and overlapping interactions for each lipid base.…”
Section: Introductionmentioning
confidence: 99%
“…Topics that are beyond the scope of this article include molecular and nanoparticle designs that promote membrane permeation, 5 amphiphilic nanoparticles that alter membrane curvature, 6 T h i s c o n t e n t i s detailed biosynthetic pathways that produce membraneanchored proteins, 7 and molecular probes for the study of membrane diffusion and lipidomics. 8 In terms of presentation format, the article starts by briefly reviewing the various ways that Nature anchors proteins in a cell membrane, and then describes the strategies that chemical biologists use to fluorescently label a membrane protein in living cells. The latter sections describe bioconjugation methods that anchor synthetic conjugates in liposome membranes or cell plasma membranes and includes a section on switchable anchors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The article focuses on the different biosynthetic, semisynthetic, and synthetic strategies that are used to prepare an anchored construct, and we summarize the overarching concepts that underlie the molecular designs with citations directing the interested reader to the specialized synthetic and technical publications. Topics that are beyond the scope of this article include molecular and nanoparticle designs that promote membrane permeation, amphiphilic nanoparticles that alter membrane curvature, detailed biosynthetic pathways that produce membrane-anchored proteins, and molecular probes for the study of membrane diffusion and lipidomics …”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have shown that both covalent and non-covalent fluorescent labeling is a highly sensitive strategy for studying a wide variety of biomolecules including enzymes, proteins, nucleic acids and glycans. [20][21][22][23][24][25][26][27][28] Several bioorthogonal reactions have been devised to enable fluorescence labeling to be performed under physiological conditions, within organisms, and without interfering with concurrent biochemical reactions or causing harm to organisms or target biomolecules. [29][30][31][32][33][34][35] Moreover, increasing attention has been given to applications of bioorthogonalbased fluorescent labeling to visualization cells in in vivo settings.…”
Section: Introductionmentioning
confidence: 99%